Understanding of the normalization and singularization features inscribed on the bodies of the children’s dancers of the Danza Kapital Company - Nieves Gil, Angélica del Pilar; Rojas Muñoz, Jenny Mercedes (Universidad Antonio Nariño, 2021)
The comprehensions presented below are the result of the systematization of the training experience in children’s dance of the Dance Kapital Company, whose main interest was the development of the conceptions of the children’s body that have been built up throughout its history. The conception of the body was the subject of studyfrom two categories: singularization and normalization, which are composed of attributes, the latter are the result of the voice of the actors in dialogue with authors, concepts and constructs analyzed in the research line, body, power and subjectivity of the Master’s degree in Educational and Social Development of the National Pedagogical University in the agreement with the CINDE.